Exploring Network Enabled Airspace Integration Functions for a UAV Mission Management Station - Koeners, G.J.M.; De Vries, M.F.L.; Goossens, A.A.H.E.; Tadema, J.; Theunissen, E. (2006 ieee/aiaa 25TH Digital Avionics Systems Conference, 2006)
The research project aims to explore the potential of network connectivity between a UAV control station (UCS), command and control (C2), and air traffic control (ATC) in the area of airspace integration. To support this research, a networked simulation environment has been created allowing mission-level simulations to be performed. Functions and user-interfaces have been designed to explore possibilities regarding integration with other assets, conflict prediction and resolution, dynamic re-planning, and dealing with datalink failures. In 2005 and 2006 a number of demonstrations has been performed to subject matter experts. These demonstrations have resulted in a better understanding of the opportunities, options, challenges and issues associated with the concepts